Balanço tecnológico de patentes na ferramenta de Diagrama de Ishikawa - Santos, Paulo Franklin Tavares (2019)
The Ishikawa Diagram is a quality tool that involves an orderly presentation of the sequence through primary and secondary causes using a problematic solution. One tool is implemented in various academic fields to solve fast impact problems or even the same routine through the flowchart in an enterprise process line. Thus, the present work aimed to analyze the number of filed patents using the Ishikawa tool in the patent databases of the World Intellectual Property Organization (WIPO), the National Institute of Industrial Property (INPI) and the European Patent Office. (Espacenet). For this, a methodology used in this research relied on the use of keywords that relate to customers using this tool. The search results were analyzed, interpreted and compared, generating statistical graphs that show the process of technological innovation in this field. Based on some of the results of the analysis, Brazil observes that when it observes other countries such as China with 61 filings in the three bases, it has a low number of related patents within the scope of the Ishikawa Diagram, with only 1 patent filing only. on the basis of the INPI.